John Stuart Mill on Education and Progress - Elisabete Mendes Silva (Anglo Saxonica, 2021)
John Stuart Mill, a supporter of state provision of popular and secular education at a national scale in Victorian England, believed education was a means to foster human mind development, accounting also for the future progress of mankind. Unlike other utilitarian thinkers, like Jeremy Bentham, John Stuart Mill believed that the state, in specific circumstances, should supervise education, therefore guaranteeing its quality and not only quantity. The reforms in popular and general education throughout the nineteenth century accompanied the discussion of what should be included in the curriculum of school or university studies, and of the terms defining compulsory attendance. In this context, this paper intends to explore Mill’s position on education and progress in line with his approach to liberalism and to the problems of his time. We will argue that his concept of liberal education transcended formal instruction in schools. Instead, it should continuously strive for the moral and mental well-being of humankind. By largely delving into periodicals and other writings produced during the Victorian era, we shall describe the changes popular education suffered under the sway of political reform and utilitarianism, bearing witness to the spirit of the age and to Mill’s approach to education.